The Influence of Competency and Motivation on Job Satisfaction with Work Discipline as an Intervening Variable in BPJS Employment Pematang Siantar Branch and Kisaran Branch - Satiandra Putra Dalimunthe, Ferry; Farida Ferine, Kiki (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
This research was conducted to examine the influence of competency and motivation on job satisfaction with work discipline as an intervening variable. This type of research uses quantitative, primary data sources as the data source, the collection technique used is quantitative. The population used was 80 employees. The sample used was also 80 employees using a saturated sampling technique. The research model used is method analysis. The results of this research are as follows: Work Discipline has a positive and significant effect on Job Satisfaction with an original sample value of 0.390 and ap value of 0.000 <0.05. Competence has a positive and insignificant effect on Work Discipline with an original sample value of 0.071 and ap value of 0.257 > 0.05. Competency has a positive and significant effect on Job Satisfaction with an original sample value of 0.234 and ap value of 0.001 < 0.05. Motivation has a positive and significant effect on Work Discipline with an original sample value of 0.722 and ap value of 0.000 <0.05. Motivation has a positive and significant effect on Job Satisfaction with an original sample value of 0.377 and ap value of 0.000 <0.05. Competency has an indirect positive and insignificant effect on Job Satisfaction through Work Discipline with an original sample value of 0.028 and ap value of 0.262. Motivation has a positive and significant influence on Job Satisfaction indirectly through Work Discipline with an original sample value of 0.281 and ap value of 0.000.